EVALUATION OF POTATO CULTIVARS AND BREEDING LINES FOR CAROTENOIDS CONTENT IN TUBERS - Milczarek, Dorota; Tatarowska, Beata (Plant Breeding and Seed Science, 2017)
The potato is one of the most common elements of everyday human diet due to its high nutritional and culinary value. Potato tubers provide mainly energy in the form of carbohydrates and also some other nu-trients, which include carotenoids as compounds linked to oxidation-preventing mechanisms. The main assi-milable carotenoids present in cultivated potato are lutein and zeaxanthin. Potato cultivars rich in carotenoids are a subject of increasing consideration in breeding for improvement of the nutritional quality of tubers. The paper describes the spectrophotometric method of evaluation of total and individual carotenoids content in potato tubers.